Web-Based School Information System: Design and Implementation of the SMPN 2 Mandirancan Digital Portal - Pirman Ardyansyah; Metta Mariam (MASI Mandiri Edukasi, 2026)
The digital transformation of educational institutions has increased the need for integrated and interactive school information systems. However, many secondary schools still rely on conventional information services and static websites, limiting access to information and user interaction. This study aims to develop and evaluate a web-based digital school portal integrated with an interactive chatbot at SMPN 2 Mandirancan, Indonesia. The study was conducted at a single junior secondary school, using a Research and Development approach with the Prototype model to support interactive system development informed by user feedback. The digital portal was developed using the WordPress Content Management System (CMS) and enhanced with supporting plugins to provide dynamic content management and automated information services. The developed system was evaluated using a user acceptance questionnaire with 30 respondents: 8 teachers, 2 administrative staff members, 15 students, and 5 parents. The collected data were analyzed using descriptive statistics, with the mean score calculated for each evaluation indicator. The results showed that all evaluation indicators achieved mean scores above 4.00, including usability (4.53), information quality (4.40), service efficiency (4.43), user satisfaction (4.60), and chatbot effectiveness (4.47), indicating that the developed system was feasible and well accepted by users. The findings demonstrate the feasibility and positive user acceptance of integrating the WordPress CMS and chatbot technology into a digital school portal to support interactive school information services. This study presents a practical, low-cost framework for integrating the WordPress CMS and chatbot technology into a digital school portal that provides interactive information services in resource-constrained secondary schools.